The energy subsidisation policies of Cyprus and their effect on renewable energy systems economics - Kalogirou, Soteris A. (My University, 2003)
In this paper, the energy subsidisation policies that are in effect in Cyprus are investigated with respect to their effect on renewable energy systems economics. Two subsidisation policies are investigated, those of renewable energy and fuels. These are contradictory, as one is in favour and the other is against the exploitation of renewable energies on the island, which is the declared Government policy. First, the policy measures are described and their effect on the economic viability of a solar system is investigated by means of an example. This concerns a solar industrial process heat system for which four types of collectors are considered. From the results presented it is clear that renewable energy subsidies create a positive impulse on renewable energies whereas the economic factors improve considerably when the subsidy for fuel is removed, as the expenditure made for the erection of a solar system replaces a more expensive fuel.
Keywords: Renewable energy subsidisation; Fuel subsidisation; Industrial process heat; Economics